Rate of contamination of hospital privacy curtains on a burns and plastic surgery ward: a cross-sectional study. Issue 1 (May 2017) - Shek, K.; Patidar, R.; Kohja, Z.; Liu, S.; Gawaziuk, J.P.; Gawthrop, M.; Kumar, A.; Logsetty, S.
Summary: Background: Surfaces in the patient environment may play a role in microbial transmission if they become colonized by bacteria. Patient privacy curtains are one such surface that may pose a high risk for transmission because they are high-contact surfaces, are infrequently cleaned, and healthcare workers are less likely to wash their hands after contacting inanimate objects such as curtains. Aim: To determine the amount and type of bacterial colonization of patient privacy curtains at a regional burns/plastic surgery unit. Methods: Privacy curtain contamination on the burns/plastic surgery ward was determined for two separate occasions six months apart: 23 curtains on August 2015 and 26 curtains on January 2016. Dey–Engley neutralizing agar (DENA) replicate organism detection and counting (RODAC) contact plates were used daily to sample curtains near the edge hem where they are most frequently touched. Microbial contamination was reported as cfu/cm 2 and the presence of meticillin-resistant Staphylococcus aureus (MRSA) was determined. Swabs were also taken of any open wounds and from tracheostomy sites on the ward. Findings: Curtain contamination in August 2015 was 0.7–4.7 cfu/cm 2 with 22% testing positive for MRSA, whereas contamination on January 2016 was 0.6–13.3 cfu/cm 2 with 31% of curtains testing positive for MRSA. Conclusion: Curtains on the burns/plastic surgery ward become colonized with significant quantities of bacteria. Future studies will need to address the rate of colonization and the clinical impact of this colonization to better inform cleaning protocols.